Genetic variation and differentiation between cultured and wild populations of Channa striata (Haruan) from microsatellite markers / Jothi Annavadivoo a/p Balasingam. - Balasingam, Jothi Annavadivoo (2011)
The snakehead fish (Channa striata) is a freshwater fish species indigenous to Malaysia. Channa striata (C. striata), lo cally known as Haruan is valued as a natural remedy in traditional medicine as well as a reputable source of protein. The rapid progress of scientific validation research on the therapeutic properties of the species has spurred the equally rapid expansion of commercialised products that capitalises on these unique yet beneficial qualities of C. striata. Dependence on the wild in order to meet the increasing demand on the species is no longer a feasible option whereby, deteriorating natural abundance due to anthropogenic effects and over-exploitation has left an opening for the potential growth of the aquaculture industry of C. striata in Malaysia. The present study employed seven polymorphic microsatellite loci to investigate levels of genetic variation and differentiation of C. striata at selected cultured and wild populations in peninsular Malaysia. The study included cultured populations from three separate commercial farms (Kajang, Malacca and Rawang) as well as wild populations from three different states; Johore, Kedah and Pahang located at southern-, northern- and eastern-region of the peninsular, respectively. The results showed that cultured populations (mean number of alleles per locus, A = 7.71–9.29; allelic richness, AR = 6.752–8.108; mean effective number of alleles per locus, ne = 3.31–4.38; observed heterozygosity, Ho = 0.24–0.98; expected heterozygosity, He = 0.33–0.88) had significantly higher genetic variation relative to the wild (A = 3.86–4.86; AR = 3.843–4.838; ne = 2.01–2.20; Ho = 0.07–0.90; He = 0.07–0.69) populations. However, AMOVA analysis revealed that the greater percentage of variation (79.2%) in the total genetic diversity of the surveyed populations is primarily due to differences at the individual level and neither between, nor within, pooled cultured and pooled wild group. Departure from Hardy Weinberg Equilibrium (HWE) was observed in all cultured populations and the wild population of Kedah. Isolated cases of inbreeding and recent population bottleneck were detected among the cultured and wild populations. The results also displayed low to extensive genetic differentiation among the cultured and wild populations as revealed by pair-wise measures; FST, RST and